Cerium Oxide Nanoparticles Conjugated with Tannic Acid Prevent UVB-Induced Oxidative Stress in Fibroblasts: Evidence of a Promising Anti-Photodamage Agent - Regina G. Daré; Elayaraja Kolanthai; Craig J. Neal; Yifei Fu; Sudipta Seal; Celso V. Nakamura; Sueli O. S. Lautenschlager (MDPI AG, 2023)
Exposure to ultraviolet radiation induces photodamage towards cellular macromolecules that can progress to photoaging and photocarcinogenesis. The topical administration of compounds that maintain the redox balance in cells presents an alternative approach to combat skin oxidative damage. Cerium oxide nanoparticles (CNPs) can act as antioxidants due to their enzyme-like activity. In addition, a recent study from our group has demonstrated the photoprotective potential of tannic acid (TA). Therefore, this work aimed to synthesize CNPs associated with TA (CNP-TA) and investigate its photoprotective activity in L929 fibroblasts exposed to UVB radiation. CNP conjugation with TA was confirmed by UV-Vis spectra and X-ray photoelectron spectroscopy. Bare CNPs and CNP-TA exhibited particle sizes of ~5 and ~10 nm, superoxide dismutase activity of 3724 and 2021 unit/mg, and a zeta potential of 23 and −19 mV, respectively. CNP-TA showed lower cytotoxicity than free TA and the capacity to reduce the oxidative stress caused by UVB; supported by the scavenging of reactive oxygen species, the prevention of endogenous antioxidant system depletion, and the reduction in oxidative damage in lipids and DNA. Additionally, CNP-TA improved cell proliferation and decreased TGF-β, metalloproteinase-1, and cyclooxygenase-2. Based on these results, CNP-TA shows therapeutic potential for protection against photodamage, decreasing molecular markers of photoaging and UVB-induced inflammation.